Peran Istri Sebagai Pencari Nafkah Dalam Kesejahteraan Ekonomi Keluarga Perspektif Qira’ah Mubadalah Dan Maqashid Syariah - Mustaqim, Dede Al (Universitas Islam Negeri Alauddin Makassar, 2024)
The role of wives in today's society has grown significantly, including in pursuing careers outside the home. The role of the wife as breadwinner in the welfare of the household is still debated among society. This research aims to answer three main questions regarding the role of the wife as breadwinner in the family's economic welfare, namely the Qira'ah Mubjadian Faqihuddin Abdul Qodir perspective, the Maqashid Syariah perspective, and the impact of the wife's role as breadwinner on the family's economic welfare. The research method used is a qualitative approach with case studies as the focus. The research results show that, according to Qira'ah Mubjadi Faqihuddin Abdul Qodir's theory, Islam supports women to have careers in the public sphere and wives as breadwinners for the family are very permissible. The Maqashid Syariah theory emphasizes that the wife's work as a breadwinner must comply with the principles of Maqashid Syariah and have a significant positive impact on the family's economic welfare. Therefore, this research concludes that within the contemporary ijtihad framework which refers to the Qira'ah theory of Mubjadi Faqihuddin Abdul Qadir and the Maqashid Syariah theory, the role of the wife as the family breadwinner is highly permissible and even recommended to improve the family's economic welfare.